2018
DOI: 10.1002/jbm.b.34116
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of electrospun polyamide‐6 scaffolds for esophageal tissue engineering

Abstract: Artificial tissue-engineered grafts offer a potential alternative to autologous tissue grafts for patients, which can be traumatic. After decellularizing Papio hamadryas esophagus and studying the morphology and physical properties of the extracellular matrix (ECM), we generated electrospun polyamide-6 based scaffolds to mimic it. The scaffolds supported a greater mechanical load than the native ECM and demonstrated similar 3D microstructure, with randomly aligned fibers, 90% porosity, 29 μm maximal pore size,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 67 publications
0
7
0
1
Order By: Relevance
“…Considering long-term disability and poor surgery outcomes, peripheral nerve injury presents a substantial challenge to reconstructive surgeons, and autologous nerve grafts is thus a commonly employed measure [2]. Up until now, diverse natural and synthetic polymer biomaterials have been used for the development of scaffolds in the peripheral nerve tissue engineering field [3,4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Considering long-term disability and poor surgery outcomes, peripheral nerve injury presents a substantial challenge to reconstructive surgeons, and autologous nerve grafts is thus a commonly employed measure [2]. Up until now, diverse natural and synthetic polymer biomaterials have been used for the development of scaffolds in the peripheral nerve tissue engineering field [3,4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, they only have 2D-space for cell growth and low porosity, one of the main characteristics of the synthetic scaffolds, providing the diffusion and cellular infiltration of nutrients and metabolites . However, native extracellular matrix (ECM) of soft tissues consists of different shapes and sizes fibers such as collagen (1–20 μm, depending on the type of tissue), , elastin (0.1–0.2 μm), fibronectin (10 nm–1 μm), and laminin (5–10 nm), which have both structural and adhesive functions . It was therefore concluded that the electrospinning conditions of our study have an advantage over previously known methods.…”
Section: Resultsmentioning
confidence: 99%
“…From the perspective of single-layer scaffold structure, the classification mainly includes acellular matrix, membranes grafted with biomolecules, electrospinning scaffolds, micro-pattern scaffolds, etc. ( Hou et al, 2016 ; Wei et al, 2018 ; Zhuravleva et al, 2019 ; Chaitin et al, 2021 ; Levenson et al, 2021 ) ( Table 2 ). In order to accurately simulate the inner ring and outer longitudinal structure of the muscle layer, electrospinning scaffolds and micro-pattern scaffolds are mainly used ( Gong et al, 2013 ; Kuppan et al, 2017 ).…”
Section: Single-layer Esophageal Scaffoldsmentioning
confidence: 99%